Discourse(s) and controversy: some reflexions - Gil, Isabel Fuzeta (2019)
This paper draws on the complementary notions of “visée argumentative” and argumentative dimension proposed by Amossy (2012 [2000]), or, according to Micheli (2012), the narrow and broad concepts of argumentation, in order to characterize polemic discourse. Pondering on these issues necessarily leads to consider the enunciative-pragmatic and configuration dimensions of discourses. Although in a more “classic” perspective argumentation relies on logos, it is nowadays indisputable that it also relies on pathos and ethos, and that emotions play a central role in the strategy employed by the speaker/locutor to influnce the hearer/addressee and in the outlining of an antagonistic space. The analysis will focus on the “polemicity” marks (a concept proposed by Amossy) imprinted on the discursive materiality as a result of the construction of a point of view (Grize’s “éclairage”)presented to the locutor; we will analyse excerpts of speeches delivered at the Portuguese          Parliament (“Assembleia da República”) and texts published in the press the context of two referendums, bearing in mind Amossy’s notion of “argumentativity. On the other hand, we will place special emphasis on the strategies of dichotomization (Amossy, 2014) underlying the tension between ethical and ideological positions within a polemic. While it is generally understood that argumentative discourse aims to persuade/convince, this analysis shows that the dichotomization inherent to polemics may lead to an impossible intercomprehension or even to a «dialogue of deaf ears», in Angenot’s (2008) words.